Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1152/jappl.1993.74.5.2529
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nasal airflow and resistance on nasal dilator muscle activities during exercise

Abstract: Our purpose was to assess the separate effects of nasal airflow and resistance on the activity of the nasal dilator [alae nasi (AN)] muscles. Nasal airflow and the AN electromyogram were recorded at rest and during progressive-intensity exercise at 60, 120, and 150-180 W in 10 healthy subjects who breathed nasally under all conditions. The activity of the AN muscles increased linearly as a function of the increase in nasal minute ventilation evoked by progressive-intensity exercise (r = 0.99, P < 0.002). Recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…This switch commonly occurs at about 20 to 40 liter/minV E when respiratory flow is increasing in turbulence. Nevertheless, there are some subjects who maintain a predominantly nasal route of airflow into heavy intensity exercise, even though this will result in high resistance and perhaps even hypoventilation (106). Fiber optic bronchoscopy in humans has shown that the glottis normally narrows slightly during expiration while at rest, apparently to "brake" expiratory airflow and ensure preservation of EELV; however, during exercise or hyperpnea, this glottic narrowing no longer occurs (150).…”
Section: Extrathoracic Airwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…This switch commonly occurs at about 20 to 40 liter/minV E when respiratory flow is increasing in turbulence. Nevertheless, there are some subjects who maintain a predominantly nasal route of airflow into heavy intensity exercise, even though this will result in high resistance and perhaps even hypoventilation (106). Fiber optic bronchoscopy in humans has shown that the glottis normally narrows slightly during expiration while at rest, apparently to "brake" expiratory airflow and ensure preservation of EELV; however, during exercise or hyperpnea, this glottic narrowing no longer occurs (150).…”
Section: Extrathoracic Airwaysmentioning
confidence: 99%
“…The specific mechanisms for activation of the skeletal muscles of the upper airway during exercise are unknown. However, it is reasonable to suggest that activation is probably dependent on both feedforward activation of hypoglossal motor neurons in concert with descending motor output to lumbar locomotor neurons from supramedullary areas of the central nervous system (CNS), and feedback from the many sensory mechanoreceptors in the upper airway sensitive to flow, pressure, and airway deformation (106,288,404,405,572).…”
Section: Extrathoracic Airwaysmentioning
confidence: 99%
“…To that end, augmentation of nasal inspired ventilation was found to be mediated solely by increased breath frequency. More notably, increased nasal dilator muscle EMG activity observed with exercise was found to be a function of increased nasal inspired ventilation (Wheatley et al, 1991;Connel and Fregosi, 1993;Fuller et al, 1995;Sullivan et al, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…Accordingly, it has been demonstrated that activity of the nasal dilator muscles aþ ects nasal air¯ow and patency both during and after exercise (Olson and Strohl, 1987;Wheatley et al, 1991;Connel and Fregosi, 1993;Fregosi and Lansing, 1995;Sullivan et al, 1996). Olson and Strohl (1987) showed that exercise mediated a fall in nasal resistance caused by alae nasi muscle activity.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of the nasal alar muscles increases linearly as the intensity of exercise increases, probably ensuring nasal airway patency in the face of collapsing pressures [3]. Nostril dilatation increases capacity to sustain moderate exercise under nasal breathing conditions [4].…”
Section: Introductionmentioning
confidence: 99%